Management of Otomycosis in Pregnancy: A Case Study - Fierda Ovita Azhari; Gustav Syukrinto (CV. Publikasi Indonesia, 2026)
Otomycosis is a fungal infection of the external auditory canal that commonly occurs in tropical and humid regions such as Indonesia. Pregnancy is a unique physiological condition characterized by hormonal and immunological changes that may increase susceptibility to fungal infections while simultaneously limiting therapeutic options due to concerns regarding fetal safety. This report details the clinical management of a 25-year-old pregnant patient (G1P0A0) at 24 weeks gestation who presented with complaints of severe pruritus and aural fullness in the right ear. Clinical examination revealed characteristic fungal debris with a